P Potential of Karamuting (Rhodomyrtus Tomentosa) Fruit Filtrate on Reducing Ammonia Levels in Catfish (Pangasius Pangasius) (INTEGRATION PROCEEDING, 2023)
Ammonia is a chemical compound that has the molecular formula NH3 which can pollute the environment with a very pungent odor. Rivers polluted with ammonia can cause poisoning to living things around the waters. While the community often consumes Lawang fish caught from the Barito River. The decrease in ammonia levels can be reduced by using plants that contain saponin compounds, such as Karamunting which has a high level of saponin compounds in its fruit. Knowing the potential of Karamunting fruit filtrate in reducing ammonia levels in Lawang fish and the effect of different concentrations of Karamunting fruit filtrate in reducing ammonia levels in Lawang fish. This study uses True Experimental,data collection in this study with the method of observation and documentation,sampling using Purposive Sampling method, determination of Ammonia levels using phenate and Nessler methods. Determination of Ammonia reduction using the Uv-VIS spectrophotometry method. Reducing ammonia levels using Karamunting fruit filtrate on fish 1, fish 2, and fish 3. Obtained significant reduction results in samples of 25%, 50%, 75%. Fish 1 sample 25% (22.877), 50% (27.117), 75% (-6.652). Fish 2 samples 25% (7.850), 50% (16.380), 75% (19.235). Fish 3 samples 50% (2,465), 50% (7,547), 75% (16,100). The decrease in Ammonia levels occurs because Saponins have good detergent properties, so Ammonia levels can be lowered. In this study, it can be concluded that the value of the research hypothesis is 0.938, which means that the research hypothesis is rejected or there is no significant effect on differences in the concentration of Karamunting fruit filtrate on decreasing Ammonia levels in Lawang fish. In this study, 4 different concentrations were used, namely 25%, 50%, 75%, 100%, but the optimal concentration was 75%.